Neuropshychological assessment instruments for social aggression in modern foreign studies - K.M. Shipkova (Психология и право)
Context and relevance. The possibility of neuropsychological methods to identify organic cognitive impairments has increased interest in the neuropsychological aspects of aggressive behaviour. The neuropsychological assessment of cognitive and regulatory functions in individuals with aggressive behaviour is characterised by fragmentation, poor systematics, and insufficient validity regarding selection criteria. Objective. An overview of modern neuropsychological diagnostic methods for individuals prone to aggression and cognitive-behavioural disorders detected with their implementation. Methods and materials. The paper provides the classification and comparative analysis of neuropsychological diagnostic instruments used in current psychological practice for aggressive individuals. The article pays special attention to the data collected from the Delphi consensus methodology. Results. The review analyses the role and place of questionnaires in understanding the trajectory of an evaluation of aggressive behaviour patterns in the live perspective. The article presents a meaningful analysis of methods for assessing executive functions and emotional intelligence widely used in the neuropsychological assessment of individuals prone to aggression. The article draws a picture of commonly used regulatory and inhibitory process tests used in forensic neuropsychology. The review describes some widely used “Go/No-go task” paradigm and their implementation specificity for persons prone to aggression. The paper points out the specificity of emotional intelligence assessment and the difference between prosocial and antisocial personalities in emotion recognition. Conclusions. The review points out that there is a need to reach a consensus on the batteries of neuropsychological methods that are used by neuropsychologists for individuals prone to aggression and to develop scales of their normative values based on age.